2020
DOI: 10.1108/wje-09-2020-0418
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the residual stresses and deformations during the autogenous GTAW process

Abstract: Purpose The gas tungsten arc welding (GTAW) process is a widely used process that produces quality weldments. But the high heat generation from the GTAW arc can cause extreme temperatures as high as 20,000°C. The residual stresses and deformations are high accordingly. One of the methods for decreasing residual stresses and deformations is to change the welding pattern. In the literature, there are not so many examples of modeling dealing with welding patterns. This paper aims to investigate the influence of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The results of these studies showed that straight patterns and preheating can cause better results in the sense of distortions. GTAW process was also investigated by Savaş (Savaş, 2020). His findings show that diverging welding seams can cause better results in the sense of deformations and residual stresses.…”
Section: Resultsmentioning
confidence: 99%
“…The results of these studies showed that straight patterns and preheating can cause better results in the sense of distortions. GTAW process was also investigated by Savaş (Savaş, 2020). His findings show that diverging welding seams can cause better results in the sense of deformations and residual stresses.…”
Section: Resultsmentioning
confidence: 99%